(-3).(x-2)<0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x = { 1;2;3;4 }
b) x= { 0;1;2;3}
c) x= { 0;1;2;3;4 }
d) x= { -1;0;1}
e) x= { 2;3 }
f) x= { 5;6 }
g) x= { 5;6;7 }
h) x= { 3;-3;2;1;-1;-2 }
k) x= { 2;-4;0;1;-2;-3 }
l) x= { 1;2;3;8;7;9 }
o) x= { 0;1;2;-2;-3;-4 }
p) x= { 1;2;-1;-2 }
q) x= { -3;-2;-1;0;1;2 }
r) x= { 3;4;5 }
![](https://rs.olm.vn/images/avt/0.png?1311)
a: (x-3)(x-2)<0
=>x-2>0 và x-3<0
=>2<x<3
b: \(\left(x+3\right)\left(x+4\right)\left(x^2+2\right)\ge0\)
=>(x+3)(x+4)>=0
=>x+3>=0 hoặc x+4<=0
=>x>=-3 hoặc x<=-4
c: \(\dfrac{x-1}{x-2}\ge0\)
=>x-2>0 hoặc x-1<=0
=>x>2 hoặc x<=1
d: \(\dfrac{x+3}{2-x}>=0\)
=>\(\dfrac{x+3}{x-2}< =0\)
=>x+3>=0 và x-2<0
=>-3<=x<2
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : (x - 3)(x - 2) < 0
Nên sảy ra 2 trường hợp : D
Th1 : \(\hept{\begin{cases}x-3< 0\\x-2>0\end{cases}\Rightarrow\hept{\begin{cases}x< 3\\x>2\end{cases}\Rightarrow}2< x< 3}\)
Th2 : \(\hept{\begin{cases}x-3>0\\x-2< 0\end{cases}\Rightarrow\hept{\begin{cases}x>3\\x< 2\end{cases}\left(loại\right)}}\)
Vậy 2 < x < 3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x+3)(x-2)<0
=>x+3>0 và x-2<0
=>-3<x<2
=>\(x\in\left\{-2;-1;0;1\right\}\)
\(\left(-3\right).\left(x-2\right)< 0\)
Vì -3 < 0
\(=x-2>0\)
\(=x>2\)
Vậy ....